ASSESSING ECOTOURISM ECONOMICS FOR LIVELIHOOD INTERVENTION- A CASE IN NAMERI NATIONAL PARK OF ASSAM (INDIA) - Das, Niranjan; K. Sarma, Mrinmoy (ASEAN Journal on Hospitality and Tourism, 2014)
This paper entitled tries to emphasize on the ecotourism initiatives and its impact of on livelihood intervention in the fringe of Nameri National Park in Assam, India. Ecotourism initiatives that have been introduce by Assam (Bhorelli) Angling and Conservation Association (ABACA), an organization started ecotourism ventures in the year 1956 benefiting local populace in terms of income, improved infrastructure, employment opportunities and exposure. The community’s capacity to facilitate resource related conflicts has improved following support from development institutions and facilities provided by the organization. An expanding livelihood base is reducing local vulnerability to disaster and man-animal conflicts. The numbers of inhabitant wildlife species in the park have increased due to adequate protection and reduce frequency of livestock in nearby villagers. There is need to build the community’s capacity for the promotion of activities that compliment ecotourism. Through the paper the researcher emphasizes such possibilities on the basis of assessment of potential ecotourism resources of the Nameri National Park during field experience gained different parts of the study area.